Analysis of design parameters affecting the operational and embodied energy in buildings. - Jose,Jennifer (2024)
Energy efficiency in buildings can be understood elaborately by evaluating its operational and embodied energy. Embodied energy is the sum of all the energy that is used to produce materials in a building construction. This study assesses various building parameters e.g. U-value of the materials, Window to Floor Area Ratio (WFR), location, etc. that affect the operational and embodied energy and understands the optimization of the trade off between the operational and the embodied carbon impacts. The study focused on simulating three different residential building layouts in three different locations of the world. The energy simulations were performed in Design Builder and the life cycle assessment calculation was performed with etool. It is to be noted that the current study does not account for the structure of the building, material wastage, transportation of materials to the site nor the carbon required during stages of construction, demolition and subsequent re-use, recycling, or waste disposal of the materials. As, the simulations were not conducted in a detailed manner due to the various limitations of the software, hence different results could be expected based on different parameters used and the depth of the study. The results in this study indicated a better building performance in the UK compared to USA and India due to better building regulations and standards in UK focusing on creating more environment friendly and energy efficient homes. Also the higher the WFR, the higher is the GWP and the higher the operarional carbon.
Keywords: Operational Energy; Embodied Energy; Operational Carbon; Embodied Carbon